Malawi : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria, Extension and Rephasing of the Arrangement, and Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2003)
Malawi has made satisfactory economic progress under the Poverty Reduction Growth Facility (PRGF) arrangement. Executive Directors commended fiscal consolidation, structural reforms, and monetary policy, and stressed the need to maintain macroeconomic stability. They welcomed the Malawi Poverty Reduction Strategy Paper, which is aimed to attain the Millennium Development Goals. They agreed that Malawi attained the successful completion of the first review under the PRGF arrangement and approved a waiver, extension of arrangement, and an interim assistance under the Heavily Indebted Poor Countries Debt Initiative.